Enhancing Steak Taste, Juiciness, Tenderness, and Acceptability through Bromelain-Enzyme Marination: A Sensory-Focused Approach - Aziz, Fariz Nurmita; Hasniah, Nurul; Afidah, Ulil (Diponegoro University, 2025)
This study aimed to evaluate the effects of bromelain and papain proteolytic enzymes on the physicochemical and sensory properties of beef steak. Treatments included a control (P0, without proteases, papain marination for 20 minutes (P1) and 30 minutes (P2), and bromelain marination for 10 minutes (P3) and 15 minutes (P4). Parameters measured were moisture content, pH, water activity (aw), water holding capacity (WHC), color (L*, a*, b*), and sensory attributes (aroma, taste, aftertaste, juiciness, tenderness, and overall acceptability). The results showed no significant differences (p > 0.05) in moisture, pH, aw, WHC, or color across treatments. However, significant improvements were observed in sensory attributes except for the aroma. Bromelain treatment, particularly at 15 minutes, resulted in higher scores for tenderness, juiciness, and overall acceptability. Its selective proteolytic action on collagen and elastin enhanced meat texture and moisture retention without excessive protein degradation. Conversely, papain treatment led to some off-flavor development and a softer texture due to its broader proteolytic activity. In conclusion, bromelain proved more effective than papain in improving the sensory quality of beef steak. Marination with bromelain for 10–15 minutes is recommended as a natural tenderization method to enhance consumer acceptance and meat quality.